(untitled) (Acta Scientiarum. Agronomy, 2023)
Conservation practices such as no-tillage are necessary to maintain, and/or improve agricultural soil quality. However, straw formation and maintenance in tropical regions is a limiting factor to adopting this system. In this sense, this research aimed to study the effect of cover crops on straw formation, soil quality indicators, and cowpea yield under no-tillage in the Amazon savanna. Two experiments were carried out in consecutive years, on a Latossolo Amarelo. The treatments consisted of the straw of cover crops in a single (S) and intercrop (I) system, as follows: Urochloa brizantha (UBS), Pennisetum glaucum (PGS), Crotalaria juncea (CJS), Canavalia ensiformis (CES), Mucuna aterrima (MAS), U. brizantha and C. juncea (UBCJI), U. brizantha and C. ensiformis (UBCEI), P. glaucum and C. juncea (PGCJI), P. glaucum and C. ensiformis (PGCEI), and spontaneous vegetation (SV). Cowpea was cultivated after desiccation of the cover crops. Most of the straw favored soil particle aggregation, except for C. juncea and SV, which negatively influenced this variable. Basal soil respiration, organic carbon content, potassium, base saturation, geometric mean diameter, macroaggregates, and macroporosity at layer of 0-0.10 m were the most sensitive indicators for improving soil quality in a savanna environment. UBS, UBCJI, and UBCEI were superior to the other treatments in improving soil quality. Almost all treatments increased cowpea yield by up to 29%, except for CJS and SV.